Characteristics of Mineral Oil-based Nanofluids for Power Transformer Application - I. H. Zakaria; M. H. Ahmad; Y. Z. Arief; N. A. Awang; N .A. Ahmad (Institute of Advanced Engineering and Science, 2017)
Trends in the field of nanomaterial-based transformer oil show most of the conducted works have focused only on the transformer oil-based nanofluids but limited studies on the stability of transformer oil-based nanofluids. Since mineral oil-based nanofluids still can produce the sedimentation, thus the cold-atmospheric pressure plasma method is proposed to functionally modify the Silicon Dioxide (SiO2) nanofiller in order to enhance the electrical properties of the mineral oil-based nanofluids. The AC breakdown strength oil samples before and after modification were measured. It was found that the plasma treated nanofluids have higher AC breakdown voltage compared to pure oil and untreated nanofluids. Also, Fourier Transform Infrared (FTIR) Spectroscopy has been used in this study to analyse the physical changes of oil samples. It is envisaged that the added silica nanofiller has significant effect on electrical properties of the transformer oil-based nanofluids which would enable to the development of an improved class of liquid dielectric for the application of power transformer.